Flashbulb Memories for September 11th can be Preserved in Older Adults - Davidson, Patrick S. R. (2006)
Flashbulb memories (FMs) are vivid, long-lasting memories for the source of surprising, arousing news. Laboratory studies have consistently found that older adults, especially those with below-average frontal lobe (FL) function, are impaired in source memory relative to young. We tested memory for the source of news concerning the September 11th terrorist attacks in older adults with high or low frontal lobe function and in young people. We found no age differences in source memory a year after the event and no differences related to FL function. Flashbulb memories may be different from usual cases of source memory because of their emotional content, personal importance, or social relevance.